To Assess the Influence of Policy and Legal Framework On ICT Innovation - Ochola, Collins Ochieng; Agnes Nduku, Prof.Wausi (International Journal of Scientific Research and Management (IJSRM), 2021)
A study to assess the influence of policy and legal framework on Information Communication Technology (ICT) innovations in Kenya. The objective was to analyze the legal factors affecting the innovation of ICT products in Kenya with a focus was on Government regulations, Policy and Industry related factors, Copyright Infringement and Enforcement regime. Purposive sampling was used for the study while the instrument for data collection was structured questionnaires. The findings are Competition amongst major industry players’ influences innovation as every player wants to have a competitive advantage of other market players. Additionally, the government plays a key role in innovation through laying rules and regulation that govern industry players. Issuance of license to industry players this sets the terms of reference between the government and the entities. In view of the findings, Government regulation of ICT sector is of uttermost importance it protects the rights of players in the market, the environment as well as hold the players accountable. Forces of demand and supply regulate the available market for the innovations as innovators have the same target market hence how they position their items enable them get clients.